Clinical and metabolic consequences of a historic pathogenic lamin A/C founder variant - L. Y. Wong; T. Torfs; S. J. V. Vanherle; J. Janssen; G. R. F. Claes; S. L. V. M. Stroeks; M. M. A. Willemars; F. Schianchi; D. Kapsokalyvas; E. Weltjens; A. Swinnen; A. Strzelecka; et al. (Scientific Reports)
Abstract A novel LMNA p.(Glu105Leu) variant was identified in five families with dilated cardiomyopathy (DCM), revealed as a local founder variant originating approximately 650 years ago. Genetic testing and clinical analysis of 795 DCM patients demonstrated that probands with this variant typically present with severe DCM in their sixties, characterized by high prevalence of late gadolinium enhancement, arrhythmias, and conduction disorders. Time-to-event analysis suggested a later onset of clinical symptoms compared to other LMNA variants, with a trend towards longer event-free survival. Microscopic imaging of patient fibroblasts, induced pluripotent stem cell-derived cardiomyocytes (iPSC-CMs), and heart tissue confirmed structural nuclear LMNA-associated abnormalities. Patient iPSC-CMs exhibited distinct sarcomeric disorganization, increased glucose uptake and glycogen content, reduced mitochondrial function and biogenesis, and delayed contractile function. These findings support the pathogenicity of the variant and demonstrate its profound impact on structural and metabolic functions in cardiomyocytes.